Understandings of disease among Pacific peoples with diabetes and end‐stage renal disease in New Zealand. (1st August 2019) - Schmidt‐Busby, Jacqueline; Wiles, Janine; Exeter, Daniel; Kenealy, Timothy
Abstract: Background: Compared with New Zealand Europeans, Pacific peoples in New Zealand develop type 2 diabetes at a higher rate and a younger age, and have 3.8 times higher incidence of end‐stage renal disease (ESRD). Objective: To investigate contextual factors that shape understandings of disease for Pacific peoples with diabetes and ESRD. Methods: Focussed ethnography. In‐depth interviews were conducted with 16 Pacific people on haemodialysis for diabetic ESRD, in Auckland, New Zealand. Study participants aged between 30 and 69 years old were of Samoan, Cook Islander, Tongan, Niuean or Tokelauan ethnicity. Thematic analysis was used to code and identify themes. Results: Participants were embedded in a multigenerational legacy of diabetes. The limited diabetes‐related education of earlier generations influenced how future generations behaved and understood diabetes. Perceptions were compounded by additional factors including the invisibility of early‐stage diabetes; misunderstandings of health risks during communication with health providers; and misunderstandings of multiple conditions' symptoms and management. Participants had limited engagement with health services until their diagnosis of ESRD acted as a trigger to change this behaviour. However, this trigger was not effective in itself—rather, it was in combination with relevant education delivered in a way that made sense to participants, given their current understandings. Conclusions: Illness representations drive choices and behaviours with respect to self‐management of diabetes and engagement with health services. Diabetes is often present in multiple generations of Pacific people; therefore, illness representations are developed and shared within a family. Changing illness representations requires engagement with the individual within a family context.